Integration of value stream mapping & discrete event simulation: A case study from Lean - Bojan Jovanoski; Robert Minovski; Marjan Todorov; Trajce Velkovski; Bojan Jovanovski (Faculty of Technical Sciences, University of Novi Sad, Serbia, 2020)
The purpose of this paper is to present the practical implementation of value stream mapping (VSM) by monitoring selected key lean parameters and using a discrete event simulation (DES) to generate scenarios for improvement of the process. The value stream mapping, as one of the basic lean tools, forms the basis for pre-senting the current state of the system and at the same time opens guidance and opportunities for improvement. The experimentation, i.e. the transition from "as is" to "to be" state of the system is driven by the discrete event simulation, which eliminates the disadvantages of the classic "pencil driven method" and replaces them with the possibilities of the simulation as a tool where it is easy to quantify the change in the system and show the benefit of implementing lean methods. The progress and transit to the future state of the system is monitored through selected key performance indicators. Various experiments have been conducted showing the methodological approach to process improvement.
Keywords: value stream mapping, lean, key performance indicators, simulation, guided VSM simulation, process capacity analysis, process improvement.